Sur les origines du concept de méthode à l’âge classique : La Ramée, Bacon et Descartes - Philippe Hamou (Revue LISA)
Our contemporary concept of method, as a formal discourse that comes before science itself and aims at directing scientific inquiry, prescribing several steps and checking-procedures, is not the concept of method that was familiar to educated 17th-century minds. In the 16th century, the French scholar Petrus Ramus (Pierre de la Ramée) was instrumental in importing the notion of “method” from rhetoric into logic. In his French Dialectic (1555) method is described as an art of disposition, which comes after “invention” and “judgment”, and explains how teachers should present and impart their (already acquired) knowledge. This pedagogical meaning was still dominant in the 17th century, even when people, in the wake of Bacon and Descartes, started to consider the notion of a “method of invention”, an expression which would have rung as an oxymoron to anyone schooled in the Ramist tradition. This paper carefully considers Descartes’s and Bacon’s use of the term “method” or “methodus”. Bacon never used it to name his own way of invention (for which he has terms such as “via”, “ratio” or “induction”), and he carefully restricted “method” to the old meaning of an art of transmission. Descartes, even though he may be considered as the inventor of the modern acceptation of method as an ars inveniendi, modelled on geometrical analysis, still retained the old pedagogical connotation – it is quite clear that, for him, acquiring new knowledge methodically was the result of some sort of self-education rather than the application of formal rules. Finally, this study may contribute to revising our standard approach to the contrast between the Baconian and the Cartesian “methods”. It is perhaps not as much epistemological as it is anthropological and maybe religious, revealing important differences in their approaches to human capabilities and the progress of science.